The Level of Creative Thinking of Prospective Mathematics Teachers in Solving Basic Geometry Problems: Analysis and Strategies - Rosita Dwi Ferdiani (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Creative thinking ability is one of the most important 21st-century skills, especially in the context of problem solving. Creative thinking involves developing and combining ideas and innovative approaches to solve problems. Creative thinking is a process that occurs when someone comes up with new ideas. This study aimed to show prospective mathematics teachers’ creative thinking in solving geometry problems. The research subject is the student class 2023 A, Department of Mathematics Education, PGRI Kanjuruhan University Malang. Type study This is a qualitative study, with the instrument being the researcher, a sheet test, guidelines for interviews, and documentation. The results are one subject study meets TKBK 2, 1 subject study meets TKBK 3, 1 subject study meets TKBK 4, and 1 subject study fulfils TKBK 5. Based on the results of the interview with the subject study with TKBK 2, 3, and 4, the conclusion is that students are not yet used to understanding and learning concepts, tangible objects, or real-world situations, so that difficult to develop creative ideas in solving geometry. Therefore, to improve the creative thinking skills of prospective mathematics teachers, a) Provide Open-Ended Practice Questions, b). Use of Learning Media, c). Project-Based Learning. Suggestions for further research are the need to study the creative thinking process of prospective mathematics teachers, so they can later determine strategies for developing the creative thinking skills of prospective mathematics teachers.